Synthesis, DFT, molecular docking, and insecticidal activities of 4-aminoantipyrine Schiff bases - Erazua, Ehimen Annastasia; Adeleke, Babatunde Benjamin (Eclética Química, 2026)
The insecticidal potential of 4-aminoantipyrine derivatives remain underexplored despite their broad scientific applications. To develop safer insecticides for stored grain protection, a series of 4-aminoantipyrine Schiff bases were synthesized and characterized using FTIR, UV-Vis, EI-MS, and ¹H NMR spectroscopy. Insecticidal activity against Tribolium castaneum, Sitophilus oryzae, and Rhyzopertha dominica was evaluated via the impregnated filter paper method. Cytotoxicity was assessed using the brine shrimp lethality test. Chemical reactivity descriptors were obtained through Density Functional Theory (DFT), while binding affinities and receptor interactions were investigated using molecular docking simulations with two target receptors. Compounds D, F, and M exhibited excellent insecticidal activity against Rhyzopertha dominica at 239.5 µg/cm², while H and K showed moderate effects. None of the synthesized compounds showed activity against Tribolium castaneum or Sitophilus oryzae. All the synthesized compounds were non-cytotoxic to regular cell lines. These findings highlight D, F, and M as promising leads for the development of next-generation grain storage pesticides.